The Magic Realist World of “Mondo” in Le Clézio’s Mondo and Other Stories - Abedin, Zaynul (Spectrum, 2022)
Born of a French mother, and an English-descent Mauritanian father, Jean-Marie Gustave Le Clézio (Le Clézio for short) often identifies himself as Franco- Mauritanian writer always on the move. In spite of his vehement repudiation of a fixed identity for himself, he has bought himself a home in Mexico, extensively travelled the length and breadth of Africa and wistfully pondered the questions of the other, especially through his representation of the locale, the flora and fauna, and the culture of the world outside Europe. This article singles out “Mondo”, arguably the most important short story of Mondo and Other Stories, to investigate how Le Clézio brings to the fore a strange yet tantalizingly familiar world through the characterization of its eponymous protagonist Mondo, a ten-year-old boy of an uncertain provenance, and exotic idiosyncrasies. In order to critique its depiction of the real world with an undercurrent of magical fictionality that shows a strong affinity towards a literary propensity deeply rooted in the so-called peripheral cultures of the world. The article takes recourse to the recent accretions of magic realism, and delves into the author’s magic realistic worldview that denounces the Western rational system of thought. Spectrum, Volume 16, June 2021: 207-217